Pengaruh Kesesuaian Kompensasi, Gaya Kepemimpinan, Perilaku Tidak Etis, dan Kompetensi terhadap Kecurangan Akuntansi dalam Perspektif Fraud Diamond - Sari, Ni Putu Devrilia; Musmini, Lucy Sri (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2022)
This research aims to examine the effect of diamond fraud elements, such as, 1) compensation suitability, 2) leadership style, 3) unethical behavior, 4) competence, toward accounting fraud. This research employed quantitative research method that use data obtained from questionnaires and measure using the Likert scale. The research’s population were all employees of LPD’s around Abiansemal Districts. Non-probability sampling method is used with purposive sampling technique in which the chairman, secretary, and treasurer as respondents. The quality of the data is examined using the validity and reliability test. The classical assumption test used are normality, multicollinearity, and heteroscedasticity tests. The data analysis method used was multiple linear regression analysis with the assistance of SPSS 26.0 for Windows. The conclusion of the research showed: 1) compensation suitability and leadership style had a significant negative effect on accounting fraud, 2) unethical behavior and competence had a significant positive effect on accounting fraud. The results of this study have implications for LPD’s and future researchers.